المعارضة السياسية في البلدان النامية "سورية أنموذج" - قدور صفاء (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The concept of the opposition was exposed to a lot of confusion and "rubber" explanations. Its rights and duties were mixed up and the vocabularies become used inaccurately sometimes intentionally. So the researcher studied the emergence of the opposition and its meaning in terms of the language and terminology. She pointed out that there are frameworks that show the limits of the oppositions work Such as the methods used by it,Whether it is peaceful or not .and the extent according to which it accomplishes the public interest and its observance to objectivity and seience. And that some of its functions are also to remedy the mistakes of the government and looking for the best solutions ,to resist the dictatorial tendencies and participate in governance and the peaceful transfer of power she added that the legal status of the opposition in the state is determined according to the social and intellectual systemic, the constitution and the nature of the governance system in it ,and that the characteristics of the national opposition are : its permanent residence within the state, possession of objective vision and an alternative project, and to refrain from taking up weapons .In the end, the researcher made projections on the Syrian situation. تعرض مفهوم المعارضة للكثير من التشويش والمطاطية، واختلطت حقوقها وواجباتها وأصبح اللفظ يستخدم بشكل غير دقيق، وأحياناً بشكل غائي، لذا درست الباحثة نشأة المعارضة، ومعناها في اللغة والاصطلاح، وأشارت إلى أن هناك أطراً تبين حدود عمل المعارضة مثل الأساليب التي تستخدمها هل هي سلمية أم لا، ومدى تحقيقها للمصلحة العامة ومراعاتها للموضوعية والعلمية، وأن من وظائفها تدارك أخطاء الحكومة والبحث عن أفضل الحلول، ومقاومة النزعات الديكتاتورية، والمشاركة بالحكم، والتداول السلمي للسلطة، وأن الوضع القانوني للمعارضة في الدولة يتحدد حسب المنظومة الاجتماعية والفكرية والدستور وطبيعة نظام الحكم فيها، وأن من خصائص المعارضة الوطنية الإقامة الدائمة داخل الدولة وامتلاكها الرؤية الموضوعية والمشروع البديل وأن تحقق المصلحة العامة وألا تستخدم السلاح، وقامت الباحثة بإسقاطات على الحالة السورية.